2023
DOI: 10.3390/antibiotics12091350
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of the Antimicrobial Peptide Gallic Acid-Polyphemusin I (GAPI)

Olivia Lili Zhang,
John Yun Niu,
Iris Xiaoxue Yin
et al.

Abstract: A novel antimicrobial peptide, GAPI, has been developed recently by grafting gallic acid (GA) to polyphemusin I (PI). The objective of this study was to investigate the antibacterial effects of GAPI on common oral pathogens. This laboratory study used minimum inhibitory concentrations and minimum bactericidal concentrations to assess the antimicrobial properties of GAPI against common oral pathogens. Transmission electron microscopy was used to examine the bacterial morphology both before and after GAPI treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Various researchers have proposed taking advantage of the antibacterial activity of gallic acid. The antibacterial mechanisms of gallic acid include bacterial-membrane pore formation, increased membrane permeability, and changes in the physicochemical properties of bacteria [ 28 , 29 ]. In addition, gallic acid can penetrate bacterial cell membranes, resulting in the inhibition of cell wall synthesis and biofilm formation, protein and enzyme inactivation, DNA damage, and oxidative stress [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have proposed taking advantage of the antibacterial activity of gallic acid. The antibacterial mechanisms of gallic acid include bacterial-membrane pore formation, increased membrane permeability, and changes in the physicochemical properties of bacteria [ 28 , 29 ]. In addition, gallic acid can penetrate bacterial cell membranes, resulting in the inhibition of cell wall synthesis and biofilm formation, protein and enzyme inactivation, DNA damage, and oxidative stress [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it should be an effective antimicrobial peptide. Our study demonstrated that GAPI can inhibit the growth of common oral pathogens and the formation of cariogenic biofilms under laboratory conditions [ 20 ]. Moreover, GAPI enhanced the remineralisation of demineralised enamel in a chemical model.…”
Section: Introductionmentioning
confidence: 99%